Varistores à base de WO3 - Revisão - Oliveira, Marcelo Moizinho; Pessoa, Pedro Alberto Pavão; Brito, Ronilson Lopes; Rangel, José Hilton Gomes; Vasconcelos, Jomar Sales; Longo, Elson [UNESP] (FapUNIFESP (SciELO), 2016)
Varistors are elements that are part of electric power transmission and distribution systems or of special electrical installations. Varistors are manufactured in a wide variety of types, depending on their application, such as low-voltage devices with a layer of a few grains of thickness and low breakdown voltage, to varistors with a breakdown voltage of several kilovolts, such as those used in the lightning arresters of electric power distribution networks. Varistors, whose physical operation has been extensively studied, share common elements such as metal-semiconductor Schottky barrier junctions. Several studies have focused on the development of varistor ceramics for high and low voltage applications, including ZnO, SnO2, TiO2, and more recently, WO3-based ceramics. Unlike the first three compositions, WO3-based ceramics present an intrinsic varistor behavior because they contain monoclinic and triclinic phases. The addition of electron donor and acceptor dopants and heat treatments in different atmospheres also alter the non-linear properties of these systems, since they affect the formation of the Schottky barrier. This paper offers a review of the literature on the new varistor ceramic composition based on tungsten oxide (WO3).
WO3-based varistors - A review
Keywords: Electrical properties; Varistors; WO3